COVID-19: da origem aos aspectos imunológicos baseados em ontologia genética - Dias, Júlia Oliveira (Universidade Federal de São Carlos, 2022)
Coronaviruses are a group of viruses that includes SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), which causes COVID-19 (coronavirus disease 2019), a disease that had its first outbreak in China in December 2019 and that rapidly spread across the globe, characterizing a pandemic declared in March 2020. SARS-CoV-2 infection can be either asymptomatic or cause mild symptoms or progress to severe or fatal cases. COVID-19 has shown particularities that increasingly demand scientists’ attention in the search for vaccines, drugs, diagnostic methods and predictors for the severity of the case, among a scenario of high numbers of infected and deaths. The immune system plays a prominent role not only in fighting infection, but also in the immunopathology of COVID-19 itself, through hypercytokinemia, known as “cytokine storm”. This dysregulated immune response can worsen the case, as well as comorbidities that include diabetes, high blood pressure, cardiovascular disease and obesity, especially in older individuals. The present work aimed to review COVID-19’s history from an immunogenetic point of view and, in extension to the literature review, we organized data from large-scale studies that identified genes/proteins with altered expression in individuals with severe COVID-19 cases, when compared to non-severe cases. Thus, we performed an analysis based on gene ontology, revealing enriched biological processes that demonstrate the importance of the functionality and regulation of the immune response.
COVID-19: from origin to immunological aspects based on genetic ontology
Keywords: COVID-19; Genética; Imunidade; Ontologia genética; Proteoma; Transcriptoma; SARS-CoV-2; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::IMUNOLOGIA; CIENCIAS DA SAUDE; CIENCIAS BIOLOGICAS::GENETICA::GENETICA HUMANA E MEDICA; CIENCIAS BIOLOGICAS::IMUNOLOGIA::IMUNOGENETICA